The Good Neighbors. Book one, Kin - Black, Holly (Graphix, 2008)
Sixteen-year-old Rue Silver, whose mother disappeared weeks ago, believes she is going crazy until she learns that the strange things she has been seeing are real, and that she is one of the faerie creatures, or Good Neighbors, that mortals cannot see.